Time to Antivenom Administration Is Not Associated With Total Antivenom Dose Administered in a Copperhead‐predominant Snakebite Population. (1st March 2015) - Gerardo, Charles J.; Scott Evans, C.; Kuchibhatla, Maragatha; Mando‐Vandrick, Jennifer; Drake May Yen, Weiying G.; Kopec, Kathryn; Lavonas, Eric J.; Bird, Steven
Abstract Objectives To prevent unnecessary antivenom administration in crotaline snakebite, observation for progression is recommended for the patient with minor envenomation whose condition is stable and not progressing. The objective of this study was to determine the association between the time from bite to initial antivenom administration (TimeAV) and the total amount of antivenom administered (TotalAV) and to determine what proportion of patients did not have progression of the envenomation syndrome and did not receive antivenom. Methods This was a retrospective chart review of patients presenting with crotaline snakebite within 24 hours from 2009 through 2012. Blinded dual‐chart abstraction and strict data point definitions were used. Spearman correlation was used to determine the association between TimeAV and TotalAV. A general linear model was used to examine this association using TimeAV categorized to early and late administration, adjusted for likely confounders. Confounders included age, extremity involved, initial severity, and year of envenomation. Results Ninety‐five eligible patients were analyzed with 45 (47%) males and a mean (±SD) age of 36.5 (±21.1) years. Eighty‐five (89%) received antivenom, with a median TimeAV of 3.3 hours (interquartile range [IQR] = 2.5 to 5.2 hours). The median TotalAV was 10 vials (IQR = 6 to 14 vials). The univariate analysis showed a small but statistically significant decrease in TotalAV given to patients treated greater than 6 hours from bite (r = –0.26, p = 0.015). The multivariate analysis resulted in no significant relation between early or late TimeAV and TotalAV (p = 0.10) after adjustment for confounders. Most minimal envenomation syndromes (80%, or 41 of 51) progressed to moderate grade envenomations. Conclusions TimeAV was not associated with TotalAV when adjusted for likely confounders and supports current recommendations to observe for progression in minor envenomation. The majority of envenomations progressed, resulting in only a small proportion of patients not eventually receiving antivenom. The authors recommend observation in an environment where the patient can be adequately reassessed for progression of the envenomation.